2014
DOI: 10.1017/jmech.2014.69
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Responses of a Spar-Type Floating Wind Turbine in High Waves

Abstract: Floating offshore wind turbines (FOWTs) can be used to exploit the enormous wind energy present over deep waters. Numerous studies have examined the dynamics of FOWTs, but few have focused on validating numerical results with experimental results, particularly for a deep draught FOWT in regions with frequent tropical storms. For this study, we developed a computer code and conducted experiments with a scale model to validate the simulation results. The computer code was first verified by comparing the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Han et al presented the external wind conditions for the design and assessment of wind turbine loading in tropical cyclone regions, and the results for the relevant turbine components were compared with the existing load envelope. Lee et al developed a computer code and conducted experiments with a scale model to validate the simulation results of floating OWTs in regions with frequent tropical storms. Chen et al conducted failure investigations of rotor blade damage, tubular tower collapse, and wind turbine (WT) under super typhoons on the southeast coast of Mainland China, and they found that the change of wind direction is critical during typhoons.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al presented the external wind conditions for the design and assessment of wind turbine loading in tropical cyclone regions, and the results for the relevant turbine components were compared with the existing load envelope. Lee et al developed a computer code and conducted experiments with a scale model to validate the simulation results of floating OWTs in regions with frequent tropical storms. Chen et al conducted failure investigations of rotor blade damage, tubular tower collapse, and wind turbine (WT) under super typhoons on the southeast coast of Mainland China, and they found that the change of wind direction is critical during typhoons.…”
Section: Introductionmentioning
confidence: 99%